Airway management in the obese patient: a literature review - Antunes, Paula de A. F.; Alencar , Guilherme Abreu de Britto Comte de (Revista de Medicina, 2023)
Introduction: Airway management in obese patients is a concern for anesthesiologists. This procedure is more difficult in this population due to anatomical and physiological changes caused by excess fat. Obese patients have pulmonary alterations that may lead to faster desaturation, which makes this group more susceptible to complications during tracheal intubation. Objective: To understand which factors are responsible for the higher incidence of difficult airway in obese patients. Methods: A survey on the DeCS platform, followed by PubMed and SciELO was carried out to identify articles related to the topic, including Randomized Clinical Trials, Systematic Reviews, Meta-Analysis and Books and Documents. A total of 20 articles in Portuguese, English and Spanish were selected. Results: Of the analyzed studies, three identified Mallampati III/IV, reduced mobility of cervical spine and limited mouth opening as risk factors for difficult airway. One study identified neck circumference as an associated factor, while the others stated that there is no relationship between neck circumference and difficult airway. Conclusion: There was no consensus in the literature regarding the risk factors for difficult airway. It is necessary to develop retrospective studies that analyze patients with difficult airway and complications, determining which factors were present and affected the procedure.